(untitled) (American Journal of Islam and Society, 2023)
I want to begin by congratulating my colleagues at the helm of the American Journal of Islam and Society (AJIS), as well as readers and contributors, that the journal is now finally Scopus-indexed. Consistently in circulation since its establishment in 1984, AJIS is now an open-access, biannual, double-blind peer-reviewed and interdisciplinary journal with global reach. Its newly acquired formal status speaks to its consistently high standards of scholarship and invites an ever-larger group of aspiring and senior scholars to publish their finest work on a variety of areas in Islamic thought and society. This issue of AJIS comprises four contributions, each exploring a different way in which Islam and society interact. Wardah AlKatiri proposes an Islamic vision to address the world’s deteriorating environmental prospects; Yousef Wahb addresses the challenge of upholding Islamic communal norms in North America; Sami al-Daghistani aspires to put the field of Islamic economics into conversation with classical Islamic ethics and spirituality; and Tabinda Khan addresses a theoretical lacuna in Western political scientists’ study of Islamism.